Risk Factors for Low Back Pain in Youth Inline Hockey Players During the Season—A Prospective Cohort Research - Antonio Cejudo; Víctor Jesús Moreno-Alcaraz; Pilar Sainz de Baranda (Children)
Background: Low back pain is one of the most common musculoskeletal complaints in team sports. A screening test can help understand why injuries occur and predict who is at risk for non-contact low back pain. The objectives of the research were (1) to create models using logistic regression analysis of limited lower-extremity ranges of motion to prospectively identify potential factors for in-season non-contact non-contact low back pain and (2) to determine a training threshold (cut-off) for the identified factors in inline hockey players. Methods: A prospective cohort research was performed with 49 male inline hockey players aged 8 to 15 years. Data were collected regarding age, body composition, sports antecedents, competition level, and lower-limb ranges of motion (ROM-SPORT battery, n = 11 tests). A prospective measurement of non-contact low back pain was performed after 1 year (outcome) by asking the players supervised by the medical staff team (questionnaire). Results: Sixteen players (32.7%) experienced non-contact low back pain during the 1-year surveillance period. The model showed a significant relationship (χ2(39) = 43.939; p < 0.001) between the low back pain and the predictor variable hip flexion with the knee extended range of motion (OR = 3.850 [large]; 95% CI = 1.293 to 11.463; p = 0.015). The Bayesian Information Criteria and the Akaike Information Criteria for model fit were 56.885 and 37.967, respectively. The training threshold for hip flexion with the knee extended of ≤67° was set, which has an acceptable (area under the curve ≥ 94.1%) discriminatory ability for the development of non-contact low back pain for the screening test. Conclusions: Hamstring extensibility at 67° or less, as determined by hip flexion with knee extension, is a predictor of non-contact low back pain in youth inline hockey players.